Pengaruh Postingan KPU Sulsel terhadap Minat Pemilih di Kalangan Mahasiswa Ilmu Komunikasi Universitas Fajar - Wahyu Kurniawan; Ira Tasya; Fitriana Fitriana (Badan Penerbit STIEPARI Press, 2025)
Social media has become one of the main channels for disseminating political information, particularly among young voters who are highly active online. The General Elections Commission (KPU) of South Sulawesi utilizes its official Instagram account, @kpusulsel, as a medium to provide election-related information and encourage political participation. This study aims to analyze the influence of KPU South Sulawesi's Instagram posts on voting interest among students of the Communication Studies Program at Fajar University. A quantitative approach with an explanatory method was applied, and data were collected through questionnaires distributed to 67 respondents using a purposive sampling technique. The analysis focused on aspects of message delivery, including the attractiveness of visuals, clarity of language, and relevance of information presented in the posts. The findings show that Instagram content from KPU South Sulawesi has a significant and positive impact on students’ voting interest. Pearson correlation analysis demonstrated a very strong relationship (r = 0.976), while simple linear regression confirmed that KPU’s Instagram posts significantly increase voting interest, as evidenced by a calculated t-value greater than the tabulated t-value. These results suggest that social media platforms such as Instagram are not only effective tools for political socialization but also function as strategic instruments for enhancing political literacy, shaping perceptions of elections, and fostering active participation among young voters. The study highlights the importance of optimizing digital communication strategies to strengthen democratic processes and build political awareness in higher education environments.